Guidelines for the integration of certifiable management systems in industrial companies - De Oliveira, Otavio Jose [UNESP] (Elsevier, 2013)
Organizations often operate in turbulent environments characterized by intense competitiveness, constant technological progress, new market requirements, and scarce natural resources. This scenario imposes the constant need for change in the operation and companies' management. The integration of certifiable management systems is an effective alternative in this sense. The objective of the present study is to propose guidelines for the integration of the ISO 9001 Quality Management System (QMS), ISO 14001 Environmental Management System (EMS) and OHSAS 18001 Occupational Health and Safety Management System (OHSMS) in industrial companies. These guidelines were developed based on a theoretical framework and on the results from fourteen case studies performed in Brazilian industrial companies. The proposed guidelines were divided into three phases: A) integration planning, b) integration development, and c) integration control and improvement.
Keywords: Industrial companies; Integrated Management System; ISO 14001; ISO 9001; OHSAS 18001; Integrated management systems; Environmental management systems; Industrial hygiene; Quality management; Integration